GAMBARAN PERILAKU SEKSUAL DAN ORIENTASI SEKSUAL MAHASISWA DI KOTA JAMBI - . yurni (Universitas Batanghari Jambi, 2016)
Teens today are undergoing rapid social change from a traditional society to the modern society, which also changed the norms, values and lifestyles. Teenagers who formerly maintained largely by families, indigenous culture and traditional values that exist, have been prone to erosion caused by rapid urbanization and industrialization. This is followed by the media revolution that is open to the diversity of lifestyles and career choices. Sex is a biological category; gender and sexual orientation is a social and psychological category. Sexuality is associated with genital and secondary sex organs. Each category is a sustainability spectrum or continuum (the horizontal direction) which is located subcategories like matrix. This study sought to describe sexual behavior and sexual orientation jambi students. The samples used were 100 students spread in the city of Jambi taken with incidental random sampling technique (39 men and 61 women). Measurements conducted by distributing questionnaires on study subjects then were calculated with the help of SPSS program to view a description based on the percentage of data Results if the data suggests sexual behavior committed students are holding hands (90%), Kiss cheeks (62%), Fingered on the chest (10%), embracing at the waist (54%), kiss lips (39%), holding on the genitals (10%), putting sex couples with still dressed / petting (5%), had sexual intercourse (8%). Sexual orientation of students in the city of Jambi around 93% of students have a heterosexual orientation (ie like the opposite sex) and about 7% had homosexual tendencies (like a kind)